PENGELOLAAN PELAKSANAAN PRAKTIK KERJA INDUSTRI PADA JURUSAN TEKNIK KENDARAAN RINGAN DI SMK NEGERI 2 BANDA ACEH - Sardimanto, Yusrizal, Niswanto (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2017)
Abstract: The industrial internship program is one of the methods to implement vocational education and training, especially at vocational high schools by integrating learning activities at schools into a direct experience in enterprises and industries, which represents the real working environment. The objective of this study was to have an overview of management, implementation, and inhibiting factors in the industrial internship program at Light Vehicle Engineering Department, State Vocational High School 2 in Banda Aceh. The method used in this research was a descriptive method with a qualitative approach. The data were collected by using observation, interview and documentation studies. The subjects in this research were the school principal, vice principal for public relation, and head of the department, teachers who were assigned to supervise the students, and representatives from enterprises and industries. The research results showed that: (1) The industrial internship program was designed by adjusting planning activities with school vision and missions, school organizational structure, and committee assigned to implement the program in accordance with their responsibilities; (2) In addition, the research results showed that the industrial internship program was divided into several structured and systematic stages; (3) The research results also showed that the supervisory activities were direct and indirect considering the nature of the program; and (4) Furthermore, it was revealed that the implementation of industrial internship program was not optimum, and the facilities available at the Light Vehicle Engineering Department, State Vocational High School 2 in Banda Aceh were not as sophisticated as those in enterprises and industries.Keywords: Management, Implementation, Inhibiting Factors, Industrial Internship ProgramAbstrak: Praktik Kerja Industri merupakan suatu cara menyelenggarakan pendidikan dan pelatihan kejuruan khususnya pada Sekolah Menengah Kejuruan dengan memadukan kegiatan belajar di sekolah dan kegiatan belajar melalui bekerja langsung pada DU/DI dengan keadaan sesungguhnya yang relevan di dunia kerja atau dunia industri. Penelitian ini bertujuan untuk mendapatkan gambaran tentang pengelolaan, pelaksanaan dan hambatan Praktik Kerja Industri pada jurusan Teknik Kendaraan Ringan di SMK Negeri 2 Banda Aceh. Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data dilakukan dengan observasi, wawancara, dan studi dokumentasi. Subjek dalam penelitian ini adalah Kepala Sekolah, Waka Humas, Ketua Jurusan, Guru Pembimbing dan pihak DU/DI. Hasil penelitian menunjukkan bahwa: (1) Penyusunan program praktik kerja industri dilakukan melalui perencanaan dengan menyelaraskan kegiatan perencanaan dengan visi misi sekolah serta struktur organisasi dan pelaksana program prakerin sesuai dengan tugas dan tanggung jawab; (2) Pelaksanaan program Praktik Kerja Industri dilaksanakan dalam berbagai tahapan yang terstruktur dan sistematis; (3) Kegiatan pengawasan dilakukakan secara langsung dan tidak langsung sesuai dengan program kerja; dan (4) Hambatan yang dirasakan dari pihak internal dan eksternal sekolah dalam pengelolaan Praktik Kerja Industri masih kurang optimal dan dari segi fasilitas praktik khususnya jurusan Teknik kendaraan Ringan di SMK Negeri 2 Banda Aceh dirasakan kurang mengimbangi teknologi yang ada di DU/DI saat ini.Kata Kunci: Pengelolaan, Pelaksanaan, Hambatan, Praktik Kerja Industri